Blood Tide : a Never Land book - Barry, Dave (Disney Editions, 2008)
While investigating the strange behavior of the once-peaceful mermaids, the Lost Boys battle their old nemesis, Captain Hook, whose evil plan threatens to destroy the Mollusk village and change life on Neverland Island forever.